The Effect of Blood Donor Service Quality on Blood Donor Satisfaction in Blood Donation Unit (UDD) PMI of Surakarta City: Pengaruh Kualitas Pelayanan Donor Darah terhadap Kepuasan Pendonor Darah di Unit Donor Darah (UDD) PMI Kota Surakarta - Pangestika, Lydia Dessy; Syarifah, Syarifah (Politeknik Harapan Bangsa Surakarta, 2021)
Blood supply services in Indonesia are carried out by the Blood Transfusion Unit (BTU) and the Hospital Blood Bank (HBB). BTU is a health service facility who organized donations of blood, providers, and distribution of blood. The objective in this research is to determine the effect of the quality of blood donor services on blood donors in the Blood Donor Unit (BDD) Indonesian Red Cross Surakarta City. This research uses descriptive research method with quantitative approach and cross sectional research design. The population in this study is based on the number of 40% of the average 7,500 donors / month is 3,000 donors taken from the Blood Donor Unit (BDU) Indonesian Red Cross Surakarta City. Determination of the sample is calculated Slovin formula, with a known population of 3,000 people with an error rate of 10%, the results obtained are 100 samples. The data used is primary data obtained directly from respondents through questionnaires and processed using SPSS and Microsoft Excel. The analysis is presented in the form of frequency distribution tables and graphs. Donor satisfaction can almost completely be explained by service quality. This is evidenced by the calculation of the coefficient of determination with an R square value of 53.2%. This means that donor satisfaction can only be explained by the variable quality of blood donor services by 53.2%, the rest is influenced by other factors outside this research model. The quality of blood donation services has a significant effect on blood donor satisfaction at Blood Donor Unit (BDU) Indonesian Red Cross Surakarta City. Â Unit Transfusi Darah dan Bank Darah Rumah Sakit merupakan unit pelaksana pelayanan darah di Indonesia. Dimana berfungsi sebagai fasilitas pelayanan donor darah, menyediakan darah, dan distribusian darah. Tujuan penelitian ini adalah untuk mengetahui pengaruh kualitas pelayanan donor darah terhadap pendonor darah di Unit Donor Darah (UDD) PMI Kota Surakarta. Deskriptif kuantitatif dengan desain cross sectional diterapkan dalam penelitian ini. Populasi sebesar 3.000 pendonor di UDD PMI Kota Surakarta. Penentuan sampel dihitung menggunakan rumus slovin, dengan diketahui jumlah populasi 3.000 orang dengan tingkat kesalahan 10% maka diperoleh hasil 100 sampel. Data yang digunakan yaitu kuesioner diolah dengan SPSS dan Microsoft Excel. Analisa ditampilkan dalam tabel distribusi serta grafik. Kepuasan pendonor berhubungan erat dengan kualitas pelayanan. Dilihat dari nilai R square sebesar 53,2%. Artinya kepuasan pendonor dipengaruhi oleh variabel kualitas pelayanan donor darah sebesar 53,2%. Kualitas pelayanan donor darah berpengaruh signifikan terhadap kepuasan pendonor darah di UDD PMI Kota Surakarta.